Odpowiedzi

2009-11-30T15:51:14+01:00
A) 2x-6=5
2x=5-6
2x=-1/:2
x=-½

c)x²+2x+1+x²-4x+4=x⁴-2x+5

d)2(x²-1)= 2x²-2

e)x²-0,4x+0,04=x²+x²+0,2x+0,01
x²-0,4x+0,04-x²-x²-0,2x+0,01=0
-x²-0,6x+0,05=0

następnie delte z tego przykładu.
2009-11-30T15:51:31+01:00
2(x-3)=5
2x-6=5
2x=5+6
2x=11| :2
x=5,5
(3+x²)=x²
3+x²=x²
x²-x²=-3
0=-3
(x+1)²+(x-2)²
x²+1+x²-4
2x²-3
2(x-1)(x+1)
(2x-2)(x+1)
2x²+2x-2x-2
2x²-2
2(x-0,2)²=x²+(x+0,1)²
(2x-0,4)²=x²+x²+0,01
2x²-0,16=2x²+0,01
2x²-2x²=0,01+0,16
0=0,17
2009-11-30T15:54:19+01:00
2(x-3)=5
2x-6=5
2x=5+6
2x=11
x=5,5
2(x-1)(x+1)=2(x²-1)=2x²-2
(x+1)²+(x-2)²=x²+2x+1+x²-4x+4=2x²-2x+5
2(x-0,2)²=x²+(x+0,1)²
2(x²-0,4x+0,04)=x²+x²+0,2x+0,01
2x²-0,8x+0,08=2x²+0,2x+0,01
-0,8x-0,2x=0,01-0,08
-x=-0,07
x=0,07